"Palm oil free" vs "sustainable palm oil": the impact of claims on consumer perception. Issue 9 (1st August 2019) - Vergura, Donata Tania; Zerbini, Cristina; Luceri, Beatrice
Abstract : Purpose: The palm oil debate has become highly polarised in recent years and is of crucial importance for multinationals and their policies. The purpose of this paper is to investigate the consumers' response towards product packs communicating this food ingredient in different ways: through "palm oil free" and "with sustainable palm oil" claims or without mentioning it. Design/methodology/approach: A mail survey with a sample of 191 consumers was conducted. Respondents were equally and randomly distributed among the experimental conditions. The hypotheses were tested by a between-subjects factorial design. Findings: Results revealed that consumer exposed to the "palm oil free" products showed a lower risk perception compared to those exposed to the "with sustainable palm oil" products and to products without claim. Moreover, the product evaluation was better in the "palm oil free" condition compared to the "with sustainable palm oil" condition. No differences emerged in attitude, expected tastiness and willingness to pay. Research limitations/implications: The study sheds light on the consumer valuation of palm oil products and provides some useful managerial implications to manufacturers and product managers. Originality/value: Results enrich the literature on food claims on pre-packaged foods as the source of information and on consumers' perception towards palm oil.